Integrated Modeling to Evaluate Climate Change Impacts on Coupled Social-Ecological Systems in Alaska - Hollowed, Anne Babcock; Holsman, Kirstin Kari; Haynie, Alan C.; Hermann, Albert J.; Punt, Andre E.; Aydin, Kerim; Ianelli, James N.; Kasperski, Stephen; Cheng, Wei; Faig, Amanda; Kearney, Kelly A.; Reum, Jonathan C. P.; et al. (Frontiers in Marine Science, 2020)
The Alaska CLimate Integrated Modeling (ACLIM) project represents a comprehensive, multi-year, interdisciplinary effort to characterize and project climate-driven changes to the Eastern Bering Sea ecosystem, from physics to fishing communities. Results from the ACLIM project are being used to understand how different regional fisheries management approaches can help promote adaptation to climate-driven changes to sustain fish and shellfish populations and to inform managers and fishery dependent communities of the risks associated with different future climate scenarios. The project relies on iterative communications and outreach with managers and fishery dependent communities that has informed the selection of fishing scenarios. This iterative approach ensures that the research team focuses on policy relevant scenarios that explore realistic adaptation options for managers and communities. Within each iterative cycle, the interdisciplinary research team continues to improve: methods for downscaling climate models, climate-enhanced biological models, socio-economic modeling, and management strategy evaluation within a common analytical framework. The evolving nature of the ACLIM framework ensures improved understanding of system responses and feedbacks are considered within the projections and that the fishing scenarios continue to reflect the management objectives of the regional fisheries management bodies. The multi-model approach used for projection of biological responses facilitates the quantification the relative contributions of climate forcing scenario, fishing scenario, parameter, and structural uncertainty with and between models. Ensemble means and variance within and between models informs risk assessments under different future scenarios. The first phase of projections of climate conditions to the end of 21st century are complete, and projections of catch for core species under baseline (status quo) fishing conditions and two alternative fishing scenarios. The ACLIM modeling framework serves as a guide for multidisciplinary integrated climate impact and adaptation decision making in other large marine ecosystems.